2007
DOI: 10.1021/ja067545z
|View full text |Cite
|
Sign up to set email alerts
|

Red-, Blue-, or No-Shift in Hydrogen Bonds:  A Unified Explanation

Abstract: We provide a simple explanation for X-H bond contraction and the associated blue shift and decrease of intensity in IR spectrum of the so-called improper hydrogen bonds. This explanation organizes hydrogen bonds (HBs) with a seemingly random relationship between the X-H bond length (and IR frequency and its intensity) to its interaction energy. The factors which affect the X-H bond in all X-H...Y HBs can be divided into two parts: (a) The electron affinity of X causes a net gain of electron density at the X-H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
648
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 824 publications
(697 citation statements)
references
References 67 publications
40
648
2
7
Order By: Relevance
“…It has now been realized that there is no fundamental difference between red-and blue-shifting hydrogen bonds [129]. Joseph and Jemmis [130] have provided a unified explanation for red-, blue-, and non-shifting hydrogen bonds based on the optimum X-H bond length in the X-HؒؒؒY hydrogen bond. They have shown that the X-HؒؒؒY energy minimum could occur at longer, equal, or shorter X-H distance compared to that in the non-hydrogenbonded XH.…”
Section: Spectroscopic Evidencementioning
confidence: 99%
“…It has now been realized that there is no fundamental difference between red-and blue-shifting hydrogen bonds [129]. Joseph and Jemmis [130] have provided a unified explanation for red-, blue-, and non-shifting hydrogen bonds based on the optimum X-H bond length in the X-HؒؒؒY hydrogen bond. They have shown that the X-HؒؒؒY energy minimum could occur at longer, equal, or shorter X-H distance compared to that in the non-hydrogenbonded XH.…”
Section: Spectroscopic Evidencementioning
confidence: 99%
“…The formation of a hydrogen bond at C(2) leads to a change in the strength of the covalent C(2)-H bond, which in turn can be observed as a frequency shift of the corresponding vibrational mode. A red shift (i.e., a shift toward lower frequency or wavenumber) means a weakening of the bond, and a blue shift (i.e., a shift toward higher frequency or wavenumber) means strengthening [32].…”
Section: Vibrational Spectramentioning
confidence: 99%
“…All of these bands of CNCs exhibited slight gradual red shift compared to the relative bands of cellulose. The associated red shift occurs because the water molecules form weaker hydrogen bonding with CNCs than cellulose [11], implying that the inter-molecular hydrogen bonding of CNCs molecules are stronger. The rates of increase in the intensities, which related to the adsorption of water molecules onto C1-OH, C2-OH, C3-OH and C6-OH positions of cellulose and CNCs are shown in Fig .4.…”
Section: Fig 2 Nir Spectrum Of (A) Cellulose (B) Cncs Before and Afmentioning
confidence: 99%